Prevalence, antimicrobial resistance and phylogenetic characterization of Yersinia enterocolitica in retail poultry meat and swine feces in parts of China. (November 2018) - Peng, Zixin; Zou, Mingyuan; Li, Menghan; Liu, Danru; Guan, Wenying; Hao, Qiong; Xu, Jin; Zhang, Shuhong; Jing, Huaiqi; Li, Ying; Liu, Xiang; Yu, Dongmin; et al.
Abstract: Yersinia enterocolitica is an enteropathogen transmitted by contaminated food. In this study, a total of 500 retail poultry meat samples from 4 provinces and 145 swine feces samples from 12 provinces in China was tested for Y. enterocolitica and 26 isolates were obtained for further bio-serotyping, testing with antimicrobial susceptibility testing to a panel of antimicrobial compounds, and genetically characterization based on the whole genome sequencing. Higher prevalence (4.8%) of Y. enterocolitica contamination in retail poultry meat than that in swine feces (2.76%) was observed. No difference in bio-serotypes, multilocus sequence typing (MLST) and virulence genes distribution between swine and poultry origin were found. All isolates were resistant to ampicillin, amoxicillin/clavulanic acid, and cefazolin and were multi-drug resistant (MDR). The most predominant drug-resistance profile was AMP-CFZ-AMC-FOX (42.31%). A pathogenic isolate with bio-serotype 3/O:3 and ST135 was cultured from retail fresh chicken meat for the first time in China. Based on the whole-genome single nucleotide polymorphisms (SNPs) tree analysis, pathogenic isolates clustered closely, while nonpathogenic isolates exhibited high genetic heterogeneity. These indicated that pathogenic isolates were conserved on genetic level. The whole-genome SNP tree also revealed that Y. enterocolitica of swine, chicken and duck origin may share a common ancestor. The findings highlight the emergence of drug-resistant pathogenic Y. entrocoliticas in retailed poultry meats in China.